Pengaruh Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Pendidik di Masa Pandemi Covid-19 Di PAUD Permata Bangsa - Wiwiek Zainar Sri Utami; Eneng Garnika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to explain the effect of the supervision of the headmater to improve the pedagogical competence of teachers during the Covid 19 at PAUD Permata Bangsa. This research method is descriptive correlation, the sample sample of this research is all PAUD Permata Bangsa teachers in the academic year 2020/2021, totaling 10 teachers. The data collection technique used was a questionnaire, which was then processed through statistical analysis of SPSS version 17.00. The results showed that (1) Supervising principal are in the good category, (2) Achievement motivation of teachers are in the good category, (3) Teaching performance of teachers are in the good category, (4) supervising principal (X) has positive effect on achievement motivation teacher (Y1), (5) Teacher achievement motivation (Y1) has positive effect on the performance of teaching teachers (Y2), (6) Supervising principal (X) positive effect on the performance of teaching teachers (Y2), (7) Supervising principal (X) and Achievement motivation teacher (Y1) are jointly positive effect on the performance of teaching teachers (Y2). The conclusion is that the principal's academic supervision has a significant positive effect on the quality of education services, teacher professionalism and teacher professionalism have a positive effect on the quality of educational services. Keywords: Headmaster’s Supervision, and teachers' performance